(untitled) (Al-Qamar, 2021)
This research analyzes the life of women in Pakistan. It will explain how Pakistani women deprive of their basic rights. Many women become victims of violence in Pakistan each year. These crimes include Honor Killing, kidnapping, rape, sexual assault, and murder. The main reason for this is the patriarchal mindset, this is the idea that women are weaker than men and men have a right to rule over women. When she raises her voice, she is often suppressed and restricted. She is unable to get a proper education and live a life according to her will. First, she lives her life according to her father’s wishes and after marriage, according to her husband’s desire. Many laws were made for these women, but sadly, those laws are not obligated. Women are not treated fairly in Pakistan, and they do not get equal rights either. This paper uses, descriptive, qualitative methods and studies in which authentic studies are used.